1998
DOI: 10.1046/j.1365-3040.1998.00274.x
|View full text |Cite
|
Sign up to set email alerts
|

Repeated exposure to enhanced UV‐B radiation in successive generations increases developmental instability (leaf fluctuating asymmetry) in a desert annual

Abstract: Populations of the desert annual Dimorphotheca sinuata, derived from a common seed stock, were exposed concurrently over four successive generations to either ambient (representing no stratospheric ozone depletion) or elevated (representing 20% stratospheric ozone depletion) UV-B levels during their complete life cycle. Leaf fluctuating asymmetry (FA) was measured in populations of plants grown from seeds of selected generations which had experienced different UV-B exposure histories, and from seeds collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 28 publications
1
7
0
1
Order By: Relevance
“…These findings are corroborated by evidence of a progressive alteration in offspring performance with cumulative generations of enhanced UV‐B exposure. Also, they are supported by previously published findings of a simple linear dose–response relationship between the number of enhanced UV‐B exposure iterations in seed parentage of offspring and their leaf fluctuating asymmetry, an indirect measure of developmental instability indicating genetic damage ( Midgley et al . 1998 ).…”
Section: Discussionsupporting
confidence: 79%
“…These findings are corroborated by evidence of a progressive alteration in offspring performance with cumulative generations of enhanced UV‐B exposure. Also, they are supported by previously published findings of a simple linear dose–response relationship between the number of enhanced UV‐B exposure iterations in seed parentage of offspring and their leaf fluctuating asymmetry, an indirect measure of developmental instability indicating genetic damage ( Midgley et al . 1998 ).…”
Section: Discussionsupporting
confidence: 79%
“…Previous studies have found elevated levels of FA in organisms subjected to stress during embryonic development, including acidic conditions (Jagoe & Haines, 1985; Ostbye et al , 1997; Mazzi & Bakker, 2001), exposure to UV radiation (Midgley et al , 1998), food deprivation (Swaddle & Witter, 1994; Roy & Stanton, 1999; Stoks, 2001) and temperature fluctuations (Beardmore, 1960; Gest et al ., 1986; Clarke & McKenzie, 1992; Leary et al , 1992; Hosken et al ., 2000). Since these factors can generate FA in newly emerging young, we expected to see elevated FA in juvenile stickleback in the small bog lakes of the lowlands, as these are acidic, dystrophic and shallow.…”
Section: Discussionmentioning
confidence: 99%
“…It is also interesting to note that the Namaqualand annuals Dimorphotheca pluvialis and Dimorphotheca sinuata show some resilience of both growth and reproductive output under elevated UV-b levels, and little impact on these performance measures by elevated CO 2 levels (Wand et al, 1996), although there is some evidence to suggest a gradual accumulation of genetic damage under these conditions (Midgley et al, 1998;Musil, 1996;Musil et al, 1999). Therefore, although succulent species may be susceptible to climate change impacts, it is very likely that other plant growth forms will be more resilient, and may at least persist or even thrive under changing conditions.…”
Section: Article In Pressmentioning
confidence: 99%